Fully simplify using only positive exponents. \[ \frac{4 x^{8} y^{5}}{4 x^{8} y^{2}} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
First, notice that the coefficients of 4 in the numerator and denominator cancel each other out, giving us: \[ \frac{4 x^{8} y^{5}}{4 x^{8} y^{2}} = \frac{x^{8} y^{5}}{x^{8} y^{2}}. \] Next, we can simplify the \(x^{8}\) terms. Since the bases are the same, we use the exponent rule: \[ \frac{a^m}{a^n} = a^{m-n}. \] This gives us: \[ \frac{x^{8}}{x^{8}} = x^{8-8} = x^{0}, \] and since \(x^{0} = 1\), this term simplifies to 1. Now, let's simplify the \(y\) terms: \[ \frac{y^{5}}{y^{2}} = y^{5-2} = y^{3}. \] Therefore, the entire expression simplifies to: \[ 1 \cdot y^{3} = y^{3}. \] The final simplified result, using only positive exponents, is: \[ y^{3}. \]